Opinion Construction in the Roberts Court. (29th March 2017) - Feldman, Adam
Abstract : The Supreme Court's main output is the decision on the merits. Little is known, however, about how such decisions are constructed. This article is one of the first to look at the way Supreme Court opinions are constructed by examining the impact of the core linguistic resources at the Court's disposal. It does so in a novel manner by measuring the Court's reliance on wording from parties' merits filings, amicus briefs, and lower‐court opinions between the 2005 and 2014 terms. To accomplish this goal, the article compares language in over 13, 000 documents in the Court's docket during this period with their respective majority opinions. The article then looks at the relative impact of parties' briefs and filings, amicus curiae briefs, and lower‐court opinions on the Court's majority opinion language. This article provides both macro– and microlevel analyses by locating the relative effects of these linguistic resources on the Court's overall opinion language as well as by breaking these findings down by individual justice. In the aggregate, this article finds that, of the three resources analyzed, the Court tends to use language from parties' merits briefs most frequently, then wording from lower‐court opinions, and the least from amicus briefs, but that differences in case level factors shift the relative utility of each of these three resources.